Stable Isotopes Unravel the Sources and Transport of PM2.5 in the Yangtze River Delta, China - Han Zhang; Zhenyu Hong; Lai Wei; Barry Thornton; Youwei Hong; Jinsheng Chen; Xian Zhang (Atmosphere, 2023)
To understand the sources and migration pattern of PM2.5 in the Yangtze River Delta (YRD), China, the total carbon (TC) and total nitrogen (TN) concentrations and the corresponding stable isotope ratios (δ13CTC and δ15NTN) were determined in aerosol samples simultaneously collected from August 2014 to April 2015 at three different locations (Shanghai, Ningbo, Nanjing). Ningbo and Shanghai are geographically closer, the research results precisely divide Nanjing and the other two cities into two categories. Nanjing has a higher proportion of nitrogen in PM2.5 (13.2–15.3%) than Shanghai and Ningbo (8.6–12.6%), and the correlation analysis shows that nitrogen components (mainly ammonium nitrogen) might be the main driving force for the formation of PM2.5. The isotopes were proven to be sensitive sensors to reflect the impact of special events on PM2.5. For example, compared to other seasons, δ13CTC in autumn in the three cities are relatively depleted, indicating an input from biomass combustion to PM2.5 at this time. On New Year’s Eve, three cities simultaneously observed enriched δ13CTC due to the burning of fireworks. During the Qingming Festival, abnormally depleted nitrogen isotope ratios were observed, reflecting the vehicle exhaust pollution caused by people’s short travel. Isotopes are also used to trace the transport process of PM2.5. Postponing the sampling date in Nanjing by one day increased the linear fit (r2) of δ13CTC between Nanjing and Ningbo from 0.03 to 0.75, while that of δ15NTN improved from 0.16 to 0.63, which means PM2.5 might transport from Nanjing to Shanghai and Ningbo, and the transfer time takes one day.